Optimization of energy-window settings for scatter correction in quantitative (111)In imaging: comparison of measurements and Monte Carlo simulations. - Holstensson, M; Hindorf, C; Ljungberg, M; Partridge, M; Flux, G (2007)
Activity quantification in nuclear medicine imaging is highly desirable, particularly for dosimetry and biodistribution studies of radiopharmaceuticals. Quantitative (111)In imaging is increasingly important with the current interest in therapy using (90)Y radiolabeled antibodies. One of the major problems in quantification is scatter in the images, which leads to degradation of image quality. The aim of this study was to optimize the energy-window settings for quantitative (111)In imaging with a camera that enabled acquisition in three energy windows. Experimental measurements and Monte Carlo simulations, using the SI-MIND code, were conducted to investigate parameters such as sensitivity, image contrast, and image resolution. Estimated scatter-to-total ratios and distributions, as obtained by the different window settings, were compared with corresponding simulations. Results showed positive agreement between experimental measurements and results from simulations, both quantitatively and qualitatively. We conclude that of the investigated methods, the optimal energy-window setting was two windows centered at 171 and 245 keV, together with a broad scatter window located between the photopeaks.